Effect of deposition temperature on the tribo-mechanical properties of nitrogen doped DLC thin film - Shanmugasundar, G.; Vanitha, M.; Logesh, K.; Cepova, Lenka; Elangovan, Muniyandy (Frontiers in Mechanical Engineering, 2024)
The tribomechanical characteristics of diamond-like carbon (DLC) coatings are notably superior to other hard coatings, making them highly desirable for industrial applications. This study focuses on the synthesis of nitrogen-doped DLC (N-DLC) films through chemical vapor deposition (CVD) methods, with an emphasis on varying the deposition temperature. Comprehensive characterization techniques such as atomic force microscopy (AFM), scanning electron microscopy (SEM), and nanoindentation were employed to investigate the morphological and mechanical attributes of these coatings. The thickness of the films, measured using a Dektak profilometer, demonstrated an increase from 1.9 to 2.8µm as the deposition temperature rose. Nanoindentation testing revealed that the film deposited at 900°C exhibited the highest hardness (H) and modulus of elasticity (E), measuring 21.95 GPa and 208.3 GPa, respectively. Conversely, the film deposited at 1000°C showed the lowest values, with H and E at 14.23 GPa and 141.9 GPa, respectively. The H/E ratio of the coatings initially rose from 0.096 to 0.106 as the deposition temperature increased from 800 to 900 °C. However, for deposition temperatures exceeding 900 °C the H/E ratio began to decline.